Analisis Pengaruh Kemampuan Digitalisasi Guru Terhadap Keberhasilan Kebijakan yang Diterapkan di Sekolah Dasar - Fitri, Rizka Malfiana; Khoerunnisa, Hijri; Andini, Syalsabila Eka; Herlina, Herlina; Mahmudah, Ashfa Nurul; Nurmalasari, Ulfi; Kuswandari, Erika Aryani; Alindra, Afridha Laily (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Education in the era of digital transformation in Indonesia faces new challenges and opportunities. Teachers, as the spearhead of learning, are required to have adequate digital competencies to implement technology-based education policies. This study aims to understand the role of schools and the government in improving the digital competencies of elementary school teachers. This research uses a descriptive qualitative method with open-ended questionnaire analysis to collect data from teachers at an elementary school in Purwakarta. The analysis results show that schools and the government have provided support; however, there are still obstacles such as unsustainable training and infrastructure disparities. Internal and external factors such as age, learning motivation, and internet network availability also influence the digitalization of teachers. This study recommends sustainable training strategies, mentoring, and improvement of technological infrastructure to enhance the success of digitalization policies in elementary schools. The findings indicate that digitalization can increase student interest and clarify learning materials, but its effectiveness depends on teacher readiness and student access. The study concludes that teachers’ digital capabilities play a crucial role in the successful implementation of technology-based education policies in elementary schools.